The Role of Psychological Empowerment in Reducing the Level of Occupational Burnout among Teachers - Lefkir, Ali; Hammouche, Asma; Cheikhaoui, Salaheddine (جامعة أمحمد بوقرة بومرداس - مخبر أداء المؤسسات الاقتصادية الجزائرية في ظل الحركية الاقتصادية الدولية, 2022)
Psychological empowerment is considered one of the modern concepts in the field of human behavior within organizations. Employee empowerment strategies are the basis of modern management policies in contemporary organizations. These organizations depend on the concepts of total quality, work development, employees' competence, and independence. Adopting the approach of psychological empowerment of the human resource and making him feel that he has a degree of independence and freedom in administrative practice at the level of all parts of the horizontal flexible organizational structure affects the degree of his performance as well as his belonging to the organization and achieving a degree of harmony and compatibility within the work environment. As a result, psychological empowerment is regarded as an effective tool in reducing psychological burnout in the educational, professional environment. The study aimed to identify the role of psychological empowerment in reducing the level of occupational burnout among teachers (a field study on a sample of primary school teachers in the province of Boumerdes). The descriptive-analytic method was used in order to achieve the objectives of the study. Two questionnaires have been approved after reviewing the theoretical literature on the subject of the study. The first relates to psychological empowerment, consisting of five dimensions, while the second relates to psychological burnout, which in turn also consists of three dimensions. This is after confirming their psychometric characteristics honestly and consistently. The research tool was applied to a sample of 98 teachers. And after statistically analyzing the data using the SSPS program version N. (22)
Keywords: البيئة التعليمية -- إدارة الموارد البشرية -- الإرهاق المهني -- التمكين النفسي